Identificação de superfícies geomorfológicas através do método de Isobase no Planalto Basáltico da média-baixa bacia do Rio da Várzea-RS - Zambot, Nadialine (2019)
Studies related to geomorphological surfaces have become increasingly important, because of necessity of knowing and exploring subjects that are still unknown in physical geography studies. Through scientific knowledge currently available, it is aimed to understand possible dynamics involved in the transformation and evolution of landforms. This is not only in order to study their aesthetic feature but in order to analyze processes that condition transformations on multiple time scales. This fact, therefore, provide knowledge on endogenous (i.e. tectonics, earthquakes) and exogenous factors (i.e. erosion processes, weathering) in a certain area. This work presents a study about geomorphological surface of the middle-lower Várzea river basin (RS) through isobase mapping. Isobase map is a way to show anomalous patterns that indicate possible transformations on landform shapes which occurred due to possible influences of geological structure or even because of tectonic causes. Based on scientific studies, the isobase map was made by using ArcGIS software and by classification of second and third order drainage channels based on topographic maps in a 1:100 000 scale. Isoline intersections between these channels were performed on these maps through altitude values. Such procedure was carry out in order to analyze spatial behavior of isolines and existence (or even inexistence) of landform accordingly with geological structure. In this study it was possible to identify, through the isobase mapping, five areas that shows anomalies in the isoline distribution. This fact tends to indicate an influence of structural factors on the landform pattern of the middle-lower Várzea river basin.